EFFECT OF THE ADDITION BROMELIN ENZYMES IN FEED ON GROWTH AND GRADUATION OF VANNAME SHRIMP (Litopenaeusvannamei) MAINTENANCE IN THE RECIRCULATION SYSTEM - Syafrida, Syafrida; Rusliadi, Rusliadi; Mulyadi, Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTFeed is one of the important factors influencing the growth of vanname shrimp (Litopenaeus vannamei). The protein content in paan is the main energy source which acts as a structural component of cell formation in body tissues. Therefore, feed protein has an important role in the process of vanname shrimp growth. In the digestive process, enzymes are needed to hydrolyze proteins into amino acids. This process can be enhanced by adding bromelin enzymes in the feed in vanname shrimp fries. This study aims to determine the best dose of bromelin enzyme addition to feed on the growth and survival of vanname shrimp (L. vannamei) that are maintained in the recirculation system. The method used is a completely randomized complete design (RAL) experimental method one factor with 5 treatment levels and three replications. The treatment proposed is the addition of the enzyme bromelin to the feed at a dose of P0: 0%/kg of feed, P1: 1.5%/kg of feed, P2: 2.0%/kg of feed, P3: 2.5%/kg of feed, and P4: 3%/kg of feed. The results showed that the addition of the enzyme bromelin to diets with different doses in the recirculation system affected the growth of absolute weight, specific growth rate, feed efficiency (P <0.05) but did not significantly affect the survival (SR) (P> 0.05) . The best treatment was on the administration of bromelin enzyme at a dose of 3%/kg of feed with an absolute weight yield of 2.27 g,  specific growth rate of 6.25%, feed efficiency of 96.33%, and survival (SR) of 91.67%. The range of water quality during the study in all treatments namely salinity 15 ppt, temperature 27-29.9 ° C, pH 6-7, dissolved oxygen 6.1-7.7 mg/L, and ammonia ranged from 0.03-0.09 mg/L.  Keywords: Bromelin enzyme, Litopenaeus vannamei, growth